Production Improvement of M1 Generation Garut (Maranta arundinacea) Rhizomes through Gamma Radiation Mutation - Puspita Deswina; Dody Priadi; Yashanti Berlinda Paradisa; Yuliana Galih Dyan Anggraheni; Enung Sri Mulyaningsih; Ambar Yuswi Perdani; Sri Indrayani (Biosaintifika: Journal of Biology & Biology Education, 2021)
Garut (Maranta arundinacea L.) is a tuber containing flour with a low Glycemic Index (IG) suitable for diabetics and other degenerative diseases. It needs to be developed to reduce the dependence on imports or to substitute wheat flour. The objective of the study was to obtain superior arrowroot seedlings and observe the effect of gamma-ray irradiation on the density and position of stomata on arrowroot leaves. In this research, the irradiation of five arrowroot accessions of second-generation (MV1) with gamma rays (0, 10, 20, 30, 40, and 50 Gray) was carried out to obtain mutants with superior character so that they could be used as parent plants for arrowroot flour production. The treatments administered were arrowroot accessions (V), gamma-ray radiation dose (R), and their interaction. The qualitative and quantitative characters on plant characteristics, tuber production, and arrowroot leaves' stomata were observed. The research results showed that increased production is primarily for 25-Pandeglang accession (808.33 grams) and 10 Gray (800.00 grams) of gamma ray radiation treatment. It is expected that this accession can be released as a new variety candidate after subsequent selection and evaluation in a further generation. Moreover, the dose of gamma-ray radiation is inversely proportional to the number of stomata, which will increase the photosynthesis, thus increasing the number of tubers produced.